1997
DOI: 10.1159/000111243
|View full text |Cite
|
Sign up to set email alerts
|

MAP2, Synaptophysin Immunostaining in Rat Brain and Behavioral Modifications after Cerebral Postischemic Reperfusion

Abstract: Plasticity in the central nervous system after cerebral ischemia is a controversial issue; focal cerebral ischemia produces an area of infarction that is surrounded by neurons that may respond to nearby damage by creating new synapses. In the present study the expression of the postsynaptic microtubule-associated protein 2 (MAP2) and the presynaptic marker protein, synaptophysin, was investigated by immunocytochemical techniques in the CA1 sector of hippocampus and in cerebellum of rats made ischemic by bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…BCCA occlusion causes reduction in blood flow to diverse regions of brain and contributes to associated behavioral and cognitive deficits (Tsuchiya et al 1993;Martinez et al 1997). Res (2011) 20:379-386 383 In the present study, a significant decrease (72.54%) in locomotor activity and an increase (189.59%) in beam walking latency have been observed after ischemia reperfusion, which was reversed by embelin pretreatment (25 and 50 mg/kg p.o.)…”
Section: Discussionsupporting
confidence: 51%
“…BCCA occlusion causes reduction in blood flow to diverse regions of brain and contributes to associated behavioral and cognitive deficits (Tsuchiya et al 1993;Martinez et al 1997). Res (2011) 20:379-386 383 In the present study, a significant decrease (72.54%) in locomotor activity and an increase (189.59%) in beam walking latency have been observed after ischemia reperfusion, which was reversed by embelin pretreatment (25 and 50 mg/kg p.o.)…”
Section: Discussionsupporting
confidence: 51%
“…Decrease in the synaptophysin IR is associated with brain injury and aging, possibly reflecting functional disturbances of synaptic transmission (13). The neuronal MAP2 determines stability and arrangement of neuronal microtubules.…”
mentioning
confidence: 99%
“…The occurrence of this cascade of events was also demonstrated under in vivo experimental conditions of partial and transient cerebral ischemia in rats and was indirectly confirmed by protective effects observed following treatment with drugs acting with different molecular mechanisms [41–46]. Over recent years, neuroscientists have acquired a considerable body of evidence to support the fact that the mammalian brain can adapt to injurious insults such cerebral ischemia, thus increasing the chances of survival [47, 48]. So, sublethal ischemic insults may protect tissues from subsequent insults.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous studies, carried out on the same experimental model of partial and transient cerebral ischemia, indicated that the environment of injured neurons seemed to determine the ability of axons to regenerate after injury [47, 72]. To this regard, endogenous mediators affecting vasculature such as endothelium-derived NO, inducing smooth muscle relaxation and then vasodilatation of brain vessels, might improve tissue perfusion, attenuating the ischemic insult and promoting functional recovery of the infarcted brain area.…”
Section: Discussionmentioning
confidence: 99%